Prevalence, distribution and functional significance of the -237C to T polymorphism in the IL-12Rβ2 promoter in Indian tuberculosis patients. - Vikas Kumar Verma (Public Library of Science (PLoS), 2012)
Cytokine/cytokine receptor gene polymorphisms related to structure/expression could impact immune response. Hence, the -237 polymorphic site in the 5' promoter region of the IL-12Rβ2 (SNP ID: rs11810249) gene associated with the AP-4 transcription motif GAGCTG, was examined. Amplicons encompassing the polymorphism were generated from 46 pulmonary tuberculosis patients, 35 family contacts and 28 miscellaneous volunteers and sequenced. The C allele predominated among patients, (93.4%, 43/46), and in all volunteers and contacts screened, but the T allele was exclusively limited to patients, (6.5%, 3/46). The functional impact of this polymorphism on transcriptional activity was assessed by Luciferase-reporter and electrophoretic mobility shift assays (EMSA). Luciferase-reporter assays showed a significant reduction in transcriptional efficiency with T compared to C allele. The reduction in transcriptional efficiency with the T allele construct (pGIL-12Rb2-T), in U-87MG, THP-1 and Jurkat cell lines, were 53, 37.6, and 49.8% respectively, compared to the C allele construct (pGIL-12Rb2-C). Similarly, densitometric analysis of the EMSA assay showed reduced binding of the AP-4 transcription factor, to T compared to the C nucleotide probe. Reduced mRNA expression in all patients (3/3) harboring the T allele was seen, whereas individuals with the C allele exhibited high mRNA expression (17/25; 68%, p = 0.05). These observations were in agreement with the in vitro assessment of the promoter activity by Luciferase-reporter and EMSA assays. The reduced expression of IL-12Rβ2 transcripts in 8 patients despite having the C allele was attributed to the predominant over expression of the suppressors (IL-4 and GATA-3) and reduced expression of enhancers (IFN-α) of IL-12Rβ2 transcripts. The 17 high IL-12Rβ2 mRNA expressers had significantly elevated IFN-α mRNA levels compared to low expressers and volunteers. Notwithstanding the presence of high levels of IL-12Rβ2 mRNA in these patients elevated IFN-α expression could modulate their immune responses to Mycobacterium tuberculosis.